The global law of terror organization lifespan - Goldman, Shlomo Ogen (Terrorism and political violence, 2020)
The study addresses the question of whether there is a global pattern of terror organization (TO) lifespan. Based on two datasets which include hundreds of organizations, we show that there is a global statistical law of TO lifespan distribution. This distribution describes populations of TOs in different contexts of periods, geographical locations, ideologies, etc. The data as a whole, as well as its subpopulations, seem to emerge from an exponential distribution, which is formulated as a mathematical model. This model enables the prediction of TOs’ global population decay rate. The findings were obtained by introducing a novel procedure, which formulates and validates this mathematical law for discrete empirical data. We suggest that human behavior generating informational cascades and a positive feedback loop, which influence the number of core members in a TO, may be the source of this global pattern.